FISHBOWL TECHNIQUE AND LEARNING INTEREST EFFECTS ON SPEAKING ACHIEVEMENT OF SMK SEMBAWA - Jaya Aswadi; Habibi Akhmad (JAMBI-ENGLISH LANGUAGE TEACHING, 2016)
Indonesian students are assumed to have low ability in speaking performance in terms of meaning, form, and communication aspects. This study investigated whether or not Fishbowl Technique and students’ learning interest are effective to improve students’ speaking achievement. The population of this study was 150 eleventh grade students of SMK SPP Sembawa Banyuasin. Sixty of them were taken to be the sample of the study. They were divided into experimental and control group through cluster random sampling. To collect the data of speaking achievement, the oral test was used. The criteria were interaction, pronunciation, fluency, and grammar. The findings showed that there was a significant difference in achievement before and after the treatment in the experimental group of students’ learning interest, it was shown that the sig. The significance Value was 0.000 < 0.05, it means that the students’ speaking achievement significantly increased. The test of Between-Subjects Effects analyses, the significant value of the technique (fishbowl) and the students’ learning interest were 0.936, the probability sig. of technique was 0.000, and the interaction between high, medium and low interest was 0.936 which was higher than the significant level of p-value 0.05, it means that there was no significant interaction between students’ learning interest and fishbowl technique. It could be meant that the learning interest did not contribute to improve the students’ speaking achievement when the fishbowl technique was applied. Keywords: Fishbowl, Interest, Speaking